A inserção da Química Verde nos programas de pós-graduação em Química do Brasil: tendências e perspectivas - Gomes, Vânia (2014)
This article aims at investigating ways in which the principles of Green Chemistry are included in Brazilian Graduate Programs in Chemistry. Part of the premise is: when facing today’s challenges concerning the production of knowledge and the formation of human resources focused on social and environmental sustainability, it has become necessary to reflect on topics, proposals, potentialities and limits related to Green Chemistry, which occur in the courses offered in over 40 Graduate Programs in Chemistry in the country. In almost all of these programs it is possible to observe that they include disciplines, groups, research lines and projects for development, analysis and formation which permit a rethinking of ways of creating green materials and processes in the contemporary Brazilian academic context.